Strategi Guru Pendidikan Agama Islam dalam Membina Toleransi Beragama Siswa di Sekolah Menengah Pertama - Hakiki, Hakiki (Journal of Educational Research, 2023)
This research aims to examine the strategies used by Islamic religious education teachers at SMP Negeri 03 Tungkal Ulu, Jambi Province, in forming religious tolerance in students. The issues studied are how students develop attitudes of tolerance towards various beliefs, teacher strategies for teaching religious tolerance, and identifying factors that support and hinder the formation of religious tolerance in students. This research is a qualitative research. The attitude of religious tolerance at SMPN 03 Tungkal Ulu, Jambi Province has reached a good level, with mutual respect, protection and respect for differences of opinion between individuals. PAI teacher strategies also involve inter-religious dialogue when there are differences in beliefs or when non-Islamic students take PAI lessons. Even though there are still several obstacles, the efforts made at SMPN 03 Tungkal Ulu, Jambi Province to build religious tolerance are quite encouraging. Penelitian ini bertujuan untuk mengkaji strategi yang digunakan oleh guru pendidikan agama Islam di SMP Negeri 03 Tungkal Ulu, Provinsi Jambi, dalam membentuk toleransi beragama pada siswa. Persoalan yang dikaji adalah bagaimana siswa mengembangkan sikap toleransi terhadap beragam keyakinan, strategi guru untuk mengajarkan toleransi beragama, serta mengidentifikasi faktor-faktor yang mendukung dan menghambat dalam membentuk toleransi beragama pada siswa. Penelitian ini merupakan penelitian kualitatif. Sikap toleransi beragama di SMPN 03 Tungkal Ulu Provinsi Jambi telah mencapai tingkat yang baik, dengan adanya saling menghargai, mengayomi, dan menghormati perbedaan pendapat di antara individu-individu. Strategi guru PAI juga melibatkan dialog antar beragama ketika terjadi perbedaan keyakinan atau ketika siswa non-Islam mengikuti pelajaran PAI. Meskipun masih terdapat beberapa kendala, upaya yang dilakukan di SMPN 03 Tungkal Ulu Provinsi Jambi dalam membangun toleransi beragama cukup menggembirakan.